The Gastro Protective Effect of Trigonella Foenum Graecum Seed (Methi) and Omeprazole in Experimentally Induced Gastric illcer in Rats - Afroz, Rumana; Rahman, Kazi Afzalur; Kamal, AHM Mostafa; Lotus, Mahbuba Jahan; Yesmin, Sultana; Yeasmin, Nahid; Rahman, Kazi Monisur (Journal of Dhaka Medical College, 2018)
Context : The gastric ulcer is a common gastrointestinal problem in Bangladesh. Gastric epithelium is under constant assault by a series of endogenous noxious factors, including HCl, pepsinogen / pepsin, and bile salts. In addition, a steady flow of exogenous substances such as medications, alcohol, and bacteria encounter the gastric mucosa. A highly intricate biologic system is in place to provide defense from mucosal injury and to repair any injury that may occur. From the ancient time, various plants were used in traditional medicine with reputation as efficacious remedies. The incidence of duodenal ulcer disease has been declining dramatically for the past 30 years, but the incidence of gastric ulcers appears to be increasing as a result of the widespread use of NSAIDs and low-dose aspirin. The list of plant derived modern medicine is very long now. About 33% of the drugs produced in the developed countries are derived from plants. Trigonella foenumgraecum (Fenugreek, Methi) is a herbal medicine used in many parts of world. Preliminary study on animal showed that Trigonella foenum-graecum seed has significant gastro-protective effect. A study was carried out to see the gastro-protective effect of Trigonella foenum-graecum (Fenugreek, Methi) and omeprazole in ethanol induced gastric ulcer in an experimental rats. Material and Methods: The present study was performed on 24 (twenty four) rats which were divided randomly into 4 groups each having 6 rats in the Pharmacology Department of Dhaka Medical college, Dhaka. The rats were aged between 8-10 weeks of both sexes and weighing between 180-200 gm. The study was carried out to demonstrate the gastro-protective effect of aqueous extract and ethanolic extract of Trigonella foenum-graecum seed and omeprazole on ethanol induced gastric ulcer in experimental rats. Result : Pretreatment with aqueous extract and ethanolic of Trigonella foenum-graecum seed (500mg/kg/body wt) showed very significant prevention in ethanol induced gastric ulcer in number of lesion, lesion length, lesion breadth, lesion area and lesion index. This prevention was statistically very significant (P<0.001). In this study there was no statistical significant difference was observed between aqueous and ethanolic extracts of Trigonella foenumgraecum seed in gastro-protective effects. Conclusion: The aqueous and ethanol extracts of Trigonella foenum-graecum seed and omeprazole possess gastro protective properties. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 126-131